Unexpected subdiaphragmatic benign cyst - Macarie, Melania; Pais, Alexandra; Molnar, Calin; Opaschi, Razvan Valerian; Șchiopea Zolog, Minodora Maria; Bățagă, Simona Maria; Macarie, Ioan (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Macarie M, Pais A, Molnar C, et al. Unexpected subdiaphragmatic benign cyst. Turk J Gastroenterol 2020; 31(11): 829-30.